X-ray fluorescence data of the trace fossil Rosselia 'Da'an-4' from the Pliocene Yutengping Sandstone Member in Taiwan - Liou, Yu-Hsuan; Löwemark, Ludvig; Wang, Pei-Ling; Dashtgard, Shahin E (PANGAEA, 2023)
In October 2019, the Rosselia samples were collected from outcrops beside the Da'an River in Taiwan, belonging to the early Pliocene Yutengping Sandstone Member of the Kueichulin Formation. Samples of the Rosselia were analyzed to explore the potential of the Rosselia as a natural archive for recording paleoenvironmental shifts in seabed sediment origin. X-ray fluorescence signals were collected from the samples to understand the compositional shifts in the concentric lamination of the Rosselia. The Itrax core scanner was used to conduct non-destructive XRF elemental analysis and produce semi-quantitative results in elemental content.
Keywords: ichnofossil; palaeoenvironment; Pliocene; Rosselia; sedimentary geochemistry; Taiwan; Yutengping Sandstone